Highly cost-effective removal of 2, 4-dichlorophenoxiacetic acid by peroxi-coagulation using natural air diffusion electrode. (1st May 2021) - Li, Yawei; Liu, Liwei; Zhang, Qizhan; Tang, Yunping; Zhou, Minghua
Abstract: 2, 4-dichlorophenoxiacetic acid (2, 4-D) was efficiently removed by peroxi-coagulation (PC) using natural air diffusion electrode (NADE) as the cathode. Ascribed to the higher generation of H2 O2, the 2, 4-D removal by PC using NADE was 24.6% higher than that of PC using modified graphite felt (M-GF). The TOC removal increased by 32.1% than electro-Fenton (EF) using NADE, which was due to the continuous generation of ferrous ions in PC process. Besides, the energy consumption (12.01 kWh kg −1 TOC) in PC using NADE was lower than PC using M-GF (20.51 kWh kg −1 TOC) and EF using NADE (58.95 kWh kg −1 TOC). PC also overcame the narrow pH limitation and showed relatively stable performances upon initial pH ranges of 3 - 9 when compared with EF system. In the PC using NADE, the contribution ratio of EF and electro-coagulation were 59.4% and 40.6% respectively, and a possible mechanism for the enhanced performance was explored. In addition, it eliminated the aeration device compared with traditional PC system, providing a more cost-effective alternative in treating organic wastewater.